MANAJEMEN PENDIDIKAN DALAM MENINGKATKAN KEDISIPLINAN SANTRI DI MTS ASH SHIDDIQ ISLAMIC BOARDING SCHOOL JAKARTA TIMUR - Muhammad Abdurrahman Humam; Sulthan Syahril; Yuli Habibatul Imamah (UNISAN JURNAL, 2024)
The objectives of this study are as follows: 1) Educational management planning in improving student discipline at the Baitul Qur'an Islamic Boarding School 2) Implementation of education management in improving the discipline of students at the Baitul Qur'an Islamic Boarding School. 3) Supervision of education management in improving student discipline at the Baitul Qur'an Islamic Boarding School. The type of research is descriptive research with a qualitative approach. The subject of this research is the leader of the boarding school, the principal, and the head of the dormitory, the students, while the object is education management in improving the discipline of the students. Data collection techniques using interviews, observation, and documentation Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions or verification. The results of the research are: 1) Planning: planning the goals of disciplinary education for students according to the vision, mission, and goals of the Baitul Qur'an Islamic Boarding School; making disciplinary rules for students; making guidelines for violations and penalties that will be given to disciplinary violators; and setting a schedule for disciplinary activities for students. 2) Implementation: providing direction for student discipline education; motivating students to participate in student discipline education; leading the course of student discipline education; communicating with students to ensure student discipline education understanding; and making decisions on actions that violate student discipline. 3) Supervision: direct supervision includes court and attendance readings; indirect supervision includes performance evaluation.